The evaluation of hyperglycemic crises in patients with ischemic heart disease - V. A. Korolev; M. O. Makarova; A. A. Makarov (Кубанский научный медицинский вестник)
The patients with Ischemic heart disease (IHD) who were ill since a few months till a few years have been checked-up. Fifty one patient suffering from IHD who were dispensary polyclinic treated have been medically examined. Among the examined patients there were 32 ill people with stenocardia tension of the 1st and 2 nd functional classes, 3 persons with unstable stenocardia, 11 patients with auricular fibrillation, 3 patients were with ventricular premature beats and tachycardia, atrioventricular blocks of the 3rd degree were also found in 2 patients. The majority of ill people were revealed as cardiac failure patients of 2A stage - 35 patients, as well as arterial hypertension of the 3rd stage in 44 people.Body mass index (BMI) was more than 30 kg/m2. An average age of ill people was 65 years. The condition of carbohydrate exchange in the people who were ill was controlled by way of determining the HbAlc by immunochemical method and the level of an empty stomach glucose plasm - by glucose oxidase way. It has been found out that an average level of blood glucose came up to 6,24±0,27 mmol/l. In this case an average value of glycated haemoglobin was registered as 5,95± 0,21%. An average value as for body weight Index was 30,07±4,15 kg/m2.The majority of the people madically checked had the level of low thickness lipoproteins higher than 2,6 mmol/l (100 mg/dl). Seventeen medically checked people manifested the level of high thickness lipoproteins that was more than 1.3 mmol/l (50 mg/dl). Sixteen patients had triglyceride level more than 1.7 mmol/l (150 mg/dl). Eight people out of fifteen checked up manifested an increased level of C-reactive albumen.The level of blood glucose and glycated haemoglobin was correlated with the level of aspartate transaminose. Alterations in the content of common cholesterol of blood serum for the value of 52,9%, triglycerides- for the value of 17,2% depended upon the alterations in the content of glycated haemoglobin. The conclusion has been made that Ichemic heart disease patients reveal dominating metabolic disturbances, reflect disglycemia, dislipidemia as well as obesity and all that radically aggrivates the major diseases processes.